The Incidence of Public Spending on Healthcare - O’Donnell, Owen (World Bank, 2012)
The article compares the incidence of public healthcare across 11 Asian countries and provinces, testing the dominance of healthcare concentration curves against an equal distribution and Lorenz curves and across countries. The analysis reveals that the distribution of public healthcare is prorich in most developing countries. That distribution is avoidable, but a propoor incidence is easier to realize at higher national incomes. The experiences of Malaysia, Sri Lanka, and Thailand suggest that increasing the incidence of propoor healthcare requires limiting the use of user fees, or protecting the poor Effectively from them, and building a wide network of health facilities. Economic growth may not only relax the government budget constraint on propoor policies but also increase propoor incidence indirectly by raising richer individuals’ demand for private sector alternatives.